STRATEGI BAURAN PEMASARAN DI SEKTOR KULINER PASAR TAKJIL DESA TAWANGSARI - Nilna Najataini; Muhammad Qarik Akbar Gandhi Akbar Gandhi; Mochammad syaifudin Zuhd Zuhdi; Farkhan Arya Wardhana; Mohammad Saiful Rifai (JSE: Jurnal Sharia Economica, 2026)
Contemporary Islamic economic discourse frequently highlights how Sharia business ethics are integrated into the activities of micro-entrepreneurs. This study aims to analyze the implementation of the marketing mix strategy (4P) among culinary MSMEs in the Tawangsari Village Takjil Market, Tulungagung, and to evaluate its compliance with muamalah principles. Utilizing a descriptive qualitative method with a field research approach, data were gathered through in-depth interviews with the Head of Tawangsari Village as the policy initiator and a purposive sample of 8 active culinary MSME actors. The research findings indicate that the merchants have implemented the 4P strategy synergistically and in alignment with Sharia rules. The product element meets halalan thayyiban criteria, price-setting reflects the principle of justice (al-adl) without manipulation (tadlis), the place arrangement is based on public interest (maslahah mursalah), and the promotion prioritizes honesty (shiddiq). This paper contributes theoretically to Islamic marketing management literature by integrating the analysis of formal economic protection policies at the village level (free-stall schemes) with the tactical practices of small business actors. In conclusion, enforcing muamalah values in seasonal markets proves crucial for strengthening consumer loyalty while serving as a model for clean, orderly, and sustainable community-based economic incubation.